2005
DOI: 10.1016/j.neurobiolaging.2004.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Decreased EEG synchronization in Alzheimer’s disease and mild cognitive impairment

Abstract: The hypothesis of a functional disconnection of neuro-cognitive networks in patients with mild cognitive impairment (MCI) and Alzheimer Dementia was investigated using baseline resting EEG data. EEG databases from New York (264 subjects) and Stockholm (155 subjects), including healthy controls and patients with varying degrees of cognitive decline or Alzheimer Dementia were analyzed using Global Field Synchronization (GFS), a novel measure of global EEG synchronization. GFS reflects the global amount of phase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
366
6
11

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(426 citation statements)
references
References 30 publications
43
366
6
11
Order By: Relevance
“…Besides GFS, we analyzed five alternative phase synchrony measures: Hilbert and wavelet based phase synchrony, phase coherence, evolution map approach (EMA), and instantaneous period approach (IPA). The p-value of the latter is low (p = 0.020; uncorrected), in agreement with the results of (Koenig et al, 2005), but this effect is non-significant after statistical post-correction.…”
Section: Discussionsupporting
confidence: 86%
“…Besides GFS, we analyzed five alternative phase synchrony measures: Hilbert and wavelet based phase synchrony, phase coherence, evolution map approach (EMA), and instantaneous period approach (IPA). The p-value of the latter is low (p = 0.020; uncorrected), in agreement with the results of (Koenig et al, 2005), but this effect is non-significant after statistical post-correction.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, MCIs showed a higher synchronization in the gamma band between right anterior and central areas, which was related to a poorer performance in attention, memory, and executive function, while in the control group, this increase was localized in more posterior regions and was directly correlated with a greater hippocampal volume and higher scores in MMSE, Immediate and Delayed Recall, and Semantic Fluency. Most of these findings, and especially the decrease in synchronization in alpha and beta bands, are in agreement with those found in MCI and AD studies (Berendse et al 2000;Jelic et al 2000;Koenig et al 2005;Stam et al 2003;Moretti et al 2008;Gómez et al 2009), suggesting that MCI could be considered as the beginning of the "disconnection syndrome" (Delbeuck et al 2003). …”
Section: Control Group Vs MCI Groupsupporting
confidence: 88%
“…At a structural level, anatomical links in AD patients are disrupted, and this has been associated with a neurofibrillary pathology (Braak and Braak 1991). At a functional level, a decrease in the brain interactions has been shown in several studies (Stam et al 2006Locatelli et al 1998Berendse et al 2000;Stam and van Dijk 2002;see Jeong 2004 for a review; Koenig et al 2005;SanzArigita et al 2010). The concept of functional connectivity has emerged to evaluate functional relations between brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is extensively reported that AD is considered as a 'disconnection syndrome', characterized by widespread degeneration of synapses and the death of neurons (Cook and Leuchter 1996;Delbeuck et al 2003;Tijms et al 2013). EEG coherence is a promising approach to evaluate functional cortical connections between different cortical areas of the brain (Dauwels et al 2010a, b;Koenig et al 2005;Pereda et al 2005;Stam et al 2003Stam et al , 2005. The higher the coherence is, the higher the linear synchrony is, which indicates a strong functional linkage (Dauwels et al 2010a, b;Pereda et al 2005), and even the information transmission, synergies and collaborative activity between different brain areas.…”
Section: Introductionmentioning
confidence: 99%